THE CONTEMPORARY RELEVANCE, BARRIERS AND BENEFITS OF THE DEVELOPMENT OF READING INTEREST IN LOWER SECONDARY EDUCATION - Laškova, Agnese; Ročāne, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Nowadays the importance of reading is increasing, emphasised and valued not only in the field of education, but also in the context of the development of the knowledge society. If an individual is not able to understand the meaning of a text, he is not able to analyse, critically evaluate and verify the information and facts it contains as well as to formulate own opinion. This also undermines the growth of society, because in the 21st century forming one's own opinion is a prerequisite and a cornerstone for the existence of a democratic society. It must be admitted that students` interest in reading in Latvia is decreasing rapidly: only 13% of respondents aged 15-18 read a book every day or every other day. Therefore it is important not only to put emphasis on developing reading skills, but also to promote students' interest in reading and individual reading behaviour. The aim of this publication is to describe the possibilities of promoting reading in lower secondary school as well as the theoretical and empirical aspects of students' individual interest in reading.